Visualization of the Two-Step Fusion Process of the Retrovirus Avian Sarcoma/Leukosis Virus by Cryo-Electron Tomography - Cardone, Giovanni (American Society for Microbiology, 2012)
Retrovirus infection starts with the binding of envelope glycoproteins to host cell receptors. Subsequently, conformational changes in the glycoproteins trigger fusion of the viral and cellular membranes. Some retroviruses, such as avian sarcoma/leukosis virus (ASLV), employ a two-step mechanism in which receptor binding precedes low-pH activation and fusion. We used cryo-electron tomography to study virion/receptor/liposome complexes that simulate the interactions of ASLV virions with cells. Binding the soluble receptor at neutral pH resulted in virions capable of binding liposomes tightly enough to alter their curvature. At virion-liposome interfaces, the glycoproteins are ∼3-fold more concentrated than elsewhere in the viral envelope, indicating specific recruitment to these sites. Subtomogram averaging showed that the oblate globular domain in the prehairpin intermediate (presumably the receptor-binding domain) is connected to both the target and the viral membrane by 2.5-nm-long stalks and is partially disordered, compared with its native conformation. Upon lowering the pH, fusion took place. Fusion is a stochastic process that, once initiated, must be rapid, as only final (postfusion) products were observed. These fusion products showed glycoprotein spikes on their surface, with their interiors occupied by patches of dense material but without capsids, implying their disassembly. In addition, some of the products presented a density layer underlying and resolved from the viral membrane, which may represent detachment of the matrix protein to facilitate the fusion process.